Sustentabilidade do uso de tecnologias para o cultivo de milho verde nos Tabuleiros Costeiros em Sergipe - Assunção, Sara Julliane Ribeiro (2019)
Agriculture is considered one of the activities that, when not well planned and executed, can generate negative impacts on the environment. These impacts affect both the biotic part of the ecosystem (plants and animals) and the abiotic part (soil and water). On the other hand, soil is considered a prime factor for the development of agronomic crops, as it supports the development of plants and provides water and nutrients for its development, and its management is determinant for the sustainability of farms. Inadequate soil management has as a direct effect on the reduction of productivity and profitability of crops, soil quality loss, associated with productive capacity loss. The soils of the Coastal Trails of the state of Sergipe, which have intrinsic characteristics due to chemical and physical limitations, are home to a significant part of the urban centers of the state and agricultural producing areas. Among the crops grown by small and medium-sized farmers on these soils, emphasis should be given to the cultivation of Green Maize, due to its nutritional and social importance, and to the profitability of the activity, when compared, for example, to maize grains. However, sustainable aspects related to these farms have are being threatened by the adoption of non-conservationist practices. In this way, the development of technologies suitable for the soil and climate characteristics of the region and that enhance soil quality, coupled with high productivity and profitability, are desirable when targeting sustainable agriculture. The main objective of this present work is to choose - among the technologies produced in a 20-year-long experiment at the Rural Campus of the Federal University of Sergipe in São Cristóvão-SE - those that favor the Sustainability of the Sergipe Coastal Trails. In order to do so, we assessed the agricultural productivity of the Green Maize (MV), the Soil Quality Index (IQS), and the Profitability Index (IR) of 12 cropping systems that combine three different soil management systems (Cigni (Vigna unguiculata), Crotalaria (Crotalaria juncea), Guandu (Cajanus cajan) and Milheto (Pennisetum glaucum)) and the cultivation of maize, the identification of the sustainability of cropping systems, identifying which has the best Sustainability Indicator (ISSC). The productivity was determined in terms of how many commercial of ear of MV produced; the IQS was determined using additive methodology, with transformation through scoring of the observed values of the soil properties; the IR was determined via cost and revenue analysis; and the ISSC calculated through geometric mean of the yield, IQS and IR, being considered sustainable systems of culture when ISSC is more than 0,4. Among the cultivation systems evaluated, the PD management system presented a higher number of commercial ears when compared to CC and CM, and the highest productivity was observed in Guandu/PD (38,368 ears of green maize), followed by Crotalaria / PD (33,912 ears of green maize). It was also verified that the cultivation systems altered the physical properties (Macroporosity, Microporosity, Potassium, Phosphorus, Magnesium, Aluminum, Base Sodium, Cation Exchange Capacity, Aluminum Saturation, Soil Organic Matter and Nitrogen Stock) (Microbial Activity, Carbon and Microbial Nitrogen, Microbial and Metabolic Quotient) of the soil, PRODUCING different impacts on the soil, generating different IQS. The PD soil management system presented better IQS, with the cultivation of Milheto / PD (IQS = 71,80) presenting the best IQS, as the Guandu/CC (IQS = 56.5) was the one that presented the lowest value. The soil function that had the least influence on the performance of the IQS was to store, supply and cycle nutrients, WHICH indicates that the soil where the study was developed (Dystrophic Red Yellow Argisol) has nutritional limitations for the vegetation, when agricultural activities are developed. For the IR, the Guandu/PD (IR = 52.02%) cultivation system presented a return on invested capital superior to the other evaluated treatments, showing to be the most efficient in the management of its own resources or of third parties applied in the agricultural activity, mainly with respect to to the Guandu/CC system (IR = -4.46%), which presented negative compensation of capital, which indicates that its adoption will cause losses to the farmer. The ISSC that indicates the cropping systems that best combine productivity (technical dimension), soil quality (environmental dimension) and profitability (economic dimension) shows that Guandu/PD (0,59) and Crotalária/PD (0,58 ) are the most sustainable cropping systems among those evaluated in this study for the edaphoclimatic conditions of the Sergipe Coastal Trails, as all the cultivation systems in association with the CC are considered unsustainable. THUS, the adoption of the Guandu/PD or Crotalaria/PD systems is indicated as being sustainable, adding regular IQS, IR and high productivity. for this reason, the choice of the system to be adopted must consider all aspects, and should not prevail over the others, aiming at the preservation of natural resources.